And now what do we do? The role of transactive memory systems and task coordination in action teams - Marques-Quinteiro, P.; Curral, L.; Passos, A. M.; Lewis, K. (Group Dynamics: Theory, Research, and Practice, 2013)
For emergency response teams such as SWAT (special weapons and tactics) or police tactical teams, team performance comes with life or death consequences. Nevertheless, research gives little attention to the dynamics particular to teams performing in extreme, dangerous, and stressful situations. In teams like police tactical teams the ability to coordinate members' actions and expertise, while adapting to evolving circumstances, is paramount. This study examines the combined effects of team implicit coordination and transactive memory systems on team adaptive behaviors and performance in a sample of 42 real police tactical teams. Contrary to predictions in the literature, our findings suggest that team implicit coordination can benefit performance even for teams performing nonroutine tasks. Moreover, we found that the relationship between team implicit coordination and team adaptive behaviors is strengthened by transactive memory systems. In the end, we discuss the implications of these findings and point new directions for future research.